Development of Web-Based Industrial Revolution 4.0 Implementation Monitoring System Prototype for Academic Programmes - Rohana, Sapawi; Rafeah, Wahi; Azzahrah, Anuar; N., Isa; Hamimah, Ujir; Shanti Faridah, Salleh; Hashimatul Fatma, Hashim; Ade Syaheda Wani, Marzuki; Wan Hashim, Wan Ibrahim; Fatihah, Ramli (Academy of Sciences Malaysia, 2022)
Universiti Malaysia Sarawak has moved forward to transform the conventional academic curriculum in line with Industrial Revolution 4.0 and the Ministry of Education’s aspiration for future-ready curriculum transformation in academic programmes. The process of monitoring the implementation of Curriculum 4.0 in UNIMAS academic programmes involved a significant number of documents that are done manually due to records being kept in writing, printed using files and manual form. Thus, access to information is less organised, time consumed and require storage space. Furthermore, unsystematic, ununiform reporting on transformative teaching and learning with different formatting. A proposed system is developed by using Unified Modelling Language that consists of Use–Case Diagrams, Activity Diagram and Sequence Diagrams to interact between the users. In this prototype, all lecturers are required to fill in 14 criteria covering future-ready curricula such as curriculum structure, transformative learning teaching delivery, and alternative assessments. This system replaced the manual way of managing to monitoring, recording, analysing, and reporting the implementation of curriculum 4.0 elements and criteria in academic programmes including the transformative learning and teaching delivery practices. Furthermore, this proposed system is more efficient, accurate and user-friendly compared to manual implementation.